The Influence of Leadership Style and Employee Welfare on Worker Productivity at PT. Hayyu Pratama Kaltim - Permatasari, Intan; Jubaidi, Jubaidi; Effendi, Achmad (Journal of Economics and Business UBS, 2025)
This study aims to examine the influence of leadership style and employee welfare on worker productivity at PT. Hayyu Pratama Kaltim. Work productivity is a key indicator of company performance, influenced by various internal factors, including leadership style and the level of employee welfare. This research employs a quantitative approach using a survey method. The population consists of all employees of PT. Hayyu Pratama Kaltim, with the sample determined using the Slovin formula. The sample in this study consisted 48 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression to assess the effect of each independent variable on the dependent variable. The results indicate that both leadership style and employee welfare have a significant influence on worker productivity, both partially and simultaneously. These findings highlight the importance of implementing effective leadership styles and addressing employee welfare to enhance workforce productivity.